Evolution of techno-nationalism: The role of the space factor - Liudmyla Zhuravlova (History of science and technology, 2023)
Technological changes of the last four decades (1980s ‒ 2020s) encourage scientists of various fields to assess the impact of technologies on the transformation of the system of international relations and national strategies of states. In particular, the main focus of many studies is devoted to the system of relations between countries with conflicting technological interests. Therefore, in the presented article, let’s focus on the theoretical understanding of the evolution of the concept of techno-nationalism. Consideration of techno-nationalism through the prism of space policy, in particular US-China relations, is appropriate from the point of view of determining the relevance of the obtained research results. In view of this, the research methodology is based on an interdisciplinary approach, which made it possible to look at the problem through the perspective of historical, economic, political sciences and the theory of international relations. The analysis of publications on this issue shows that the development of techno-nationalism took place in a dichotomous relationship with techno-globalism. In the context of the end of the Cold War, techno-nationalism was used to refer to the protectionist policies of states that opposed the free exchange of technology. Space technology, which is an indicator of leadership and has a dual purpose, has become an important element of interstate communication in the post-bipolar era. Changes in this system led to an attempt by the United States to balance the interests of national security and commercial benefits from the use of space. However, these efforts led to a further strengthening of the export control regime from the second half of the 1990s. These restrictions were mainly based on concerns about the transfer of space technology to China, which was showing signs of military modernization. Thus, the leadership challenge facing the US and China in the space industry continued to strengthen the techno-nationalist elements of innovation systems throughout the 2000s and 2010s. Based on the views of the studied scientists, the author of the article provides his own definition of techno-nationalism as a state policy, scientific approach and ideology where national factors play a key role. The results of the study showed that the components of technological systems can be affected by the process of globalization to varying degrees. And therefore, techno-globalism and techno-nationalism are components of these systems and demonstrate interdependence. In this light, such categories as digital nationalism, digital identity, and techno-authoritarianism need further development.